(untitled) (Fiep Bulletin - online, 2015)
This study aimed to report on some experiences of interventions-actions, in the area of Physical Education through the game (corporal cards) suggested by the group of study and taught in the school involving the community. The Interdisciplinary Center for Studies on Violence and Health (NIEVS) of the Universidade Estadual de Feira de Santana (UEFS), conducted an action research titled "Diagnostic Strategies of Violence and Peacebuilding in Municipal Schools of Feira de Santana," the second largest city in the state of Bahia, known as the "Princess of the Wilderness" in 36 municipal schools in the period from 2011 to 2012. In the experiences of teaching practices through the game, developed in this study, subjects experienced relationships that favored collective constructions creation of ideas that can be transferred to a shared understanding. The school needs new possibilities for teaching practices, proposing activities that arouse the interest and motivation of students through a variety of playful shapes, among them, the games, with the purpose of mediating significantly to the construction of knowledge. This discovery will appreciate the reflections on educational practices, encouraging those involved in the ways of new encounters, for peacebuilding in school.